An ethnobiological study on traditional knowledge associated with black-boned sheep (Ovis aries) in Northwest Yunnan, China - Yanxiao Fan (Journal of Ethnobiology and Ethnomedicine, 2022)
Abstract Background Black-boned sheep is a precious genetic resource with black quality traits cultivated by the Pumi people in Tongdian Town, Lanping County, Nujiang Lisu Autonomous Prefecture, Northwest Yunnan, China. It has been included in the “National Breed List of Livestock and Poultry Genetic Resources.” The local communities have a deep understanding of black-boned sheep. The traditional knowledge of black-boned sheep is essential to their conservation and sustainable development. In spite of this, there was no information on traditional knowledge associated with black-boned sheep so far. The aim of this study wasaimed to document traditional knowledge and culture, to elucidate information about forage plants, and to investigate the conservation strategy of black-boned sheep. Method Four field surveys were conducted from July 2019 to May 2021. A total of seven villages and the Pumi Culture Museum in Lanping County are being investigated. A semi-structured interview method was used to interview 67 key informants. During the investigation, we also participated in the grazing activities of black-boned sheep, observed the appearance characteristics and the herd structure of the black-boned sheep, and demonstrated traditional knowledge regarding black-boned sheep, including grazing methods, forage plants, and related customs and habits. Results We assumed that a majority of people in the current study sites were able to could distinguish black-boned sheep from their relatives by their black bones, blue-green gums, and blue-purple anus. The local people manage their black-boned sheep based on the number of sheep by sex, age, and role in a flock in the different breeding environments. Different grazing strategies have been adopted in different seasons. Through ethnobotanical investigations, 91 species of forage plants in 30 families were identified, including herbaceous, shrubs, lianas, and trees. Among all the plant species consumed by the black-boned sheep, Rosaceae species make up the greatest number, with 16, followed by Asteraceae, with 9, and 8 species of Fabaceae and Poaceae. Considering the abundance of forage plants and the preference for black-boned sheep, Prinsepia utilis and the plants of Rubus, Berberis, and Yushania occupy dominant positions. Plants used for foraging are divided into two categories: wild and cultivated. Due to the lack of forage plants in fall and winter, the local people mainly cultivate crops to feed their black-boned sheep. In addition, the black-boned sheep is an influential cultural species in the local community and plays a prominent role in the cultural identity of the Pumi people. Conclusion Sheep play an essential role in the inheritance of the spiritual culture and material culture of the Pumi ethnic group. The formation of the black-boned sheep is inseparable from the worship of sheep by the Pumi people. With a long-term grazing process, the locals have developed a variety of traditional knowledge related to black-boned sheep. This is the experience that locals have accumulated when managing forests and grasslands. Therefore, both the government and individuals should learn from the local people when it comes to protecting black-boned sheep. No one knows black-boned sheep better than them. The foremost evidence of this is the rich traditional knowledge of breeding black-boned sheep presented by key informants.